Harnessing unexploited water resources - hydrogeology of springs in the midland regions- a case study from India - Nazimuddin, M.; Saseendran, K.; Nair, S. R.; Suvarnakumari, N. (Journal of Nepal Geological Society, 2000)
The paper describes a case study on spring development in a typical midland region of the Thiruvananthapuram District in Kerala, India. Field investigations show that there are eleven perennial springs, which can be developed as drinking water supply schemes. These springs are 'contact ' springs formed at laterite-sandstone, laterite- khondalite, and laterite-coastal alluvium. One of the springs developed between the contact of laterite and khondalite in the midland area is presented in this paper. The summer discharge of the spring is 28.800 l/day and benefits 100 local people. The paper also brings out a comparison between bored well and spring water supply scheme in this midland area.